Women Education in Pakistan: Challenges and Opportunities. - Anna Askari; Ammad Jawed; Salvat Askari (International Journal on Women Empowerment, 2022)
Background: Pakistan is a country where women's education has been a topic of discussion for decades. Despite the government's efforts to improve the literacy rate and promote education, many challenges still prevent women from gaining access to education. This research paper explores the challenges and opportunities for women's education in Pakistan and how to overcome those challenges. Methodology: The study qualitatively analyzed the existing literature on women's education in Pakistan. Using data from the Pakistan Demographic and Health Surveys, articles from Academic Journals, Reports, chapters, and Newspapers. The analysis is based on the challenges and opportunities for women's education in Pakistan. Results: Pakistan's literacy rate is 46%, with a significant urban-rural divide, with 80% literacy in urban areas and 20% in rural areas. Cultural norms and conservative attitudes towards gender roles, poverty, lack of educational facilities, security, and a scarcity of female teachers are the main challenges to women's education in Pakistan. However, the government of Pakistan is trying to improve women's education through initiatives like girls' schools, scholarships, e-learning, and technology. Conclusion: women's education in Pakistan faces numerous challenges, including cultural norms, poverty, and lack of educational facilities. However, opportunities such as government initiatives, women's empowerment, and the role of technology also exist to improve women's education. It is essential to highlight the challenges to overcome them and progress.